Acute myocardial infarction complicated by cardiogenic shock in Ukraine: multicentre registry analysis 2021–2022 - Bilchenko, Anton O.; Gritsenko, Olga V.; Kolisnyk, Volodymir O.; Rafalyuk, Oleg I.; Pyzhevskii, Andrii V.; Myzak, Yaroslav V.; Besh, Dmytro I.; Salo, Victor M.; Chaichuk, Sergii O.; Lehoida, Mykhailo O.; Danylchuk, Ihor V.; Polivenok, Ihor V. (Frontiers in Cardiovascular Medicine, 2024)
Background. Data on the results and management strategies in patients with acute myocardial infarction complicated by cardiogenic shock (AMI-CS) in the Low and Lower-Middle Income Countries (LLMICs) are limited. This lack of understanding of the situation partially hinders the development of effective cardiogenic shock treatment programs in this part of the world. Materials and methods. The Ukrainian Multicentre Cardiogenic Shock Registry was analyzed, covering patient data from 2021-2022 in 6 major Ukrainian reperfusion centres from different parts of the country. Analysis was focusing on outcomes, therapeutic modalities and mortality predictors in AMI-CS patients. Results: We analyzed data from 221 consecutive patients with CS from 6 hospitals across Ukraine. The causes of CS were ST-elevated myocardial infarction (85.1%), non-ST-elevated myocardial infarction (5.9%), decompensated chronic heart failure (7.7%) and arrhythmia (1.3%), with a total in-hospital mortality rate for CS of 57.1%. The prevalence of CS was 6.3% of all AMI with reperfusion rate of 90.5% for AMI-CS. In 23.5% of cases, CS developed in the hospital after admission. Mechanical circulatory support (MCS) utilization was 19.9% using intra-aortic balloon pump alone. Left main stem occlusion, reperfusion deterioration, Charlson Comorbidity Index > 4, and cardiac arrest were found to be independent predictors for hospital mortality in AMI-СS. (Graphic abstract) Conclusions: Despite the wide adoption of primary percutaneous coronary intervention as the main reperfusion strategy for AMI, СS remains a significant problem in LLMICs, associated with high in-hospital mortality. There is an unmet need for the development and implementation of a nationwide protocol for CS management and the creation of reference CS centers based on the country-wide reperfusion network, equipped with modern technologies for MCS.